Fortissimus robore: Martin Krpan as a case of biblical reception - David Movrin (Acta Neophilologica, 2009)
Martin Krpan z Vrha, written by Fran Levstik as a conscious experiment in prose-writing, has been interpreted variously during the last century and a half. The duel between a Slovenian peasant and a giant who comes to terrorise Vienna was in turn read by scholars as a political satire, the realisation of a literary and linguistic programme, a literary parody etc. Its motif was mostly interpreted with reference to Slavic folklore characters (Pegam and Lambergar, Prince Marko,peter Klepec etc.). The analysis according to the model devised by Vladimir Propp, however, shows striking similarities with Biblical story of David and Goliath (1 Sm 17). The reception of this motif is marked by significant political overtones, already present in antiquity and then interest ingly developed in places as diverse as sixteenth-century Florence, Prague, and the Netherlands. As attested by the sources, Levstik used this motif several limes; to a certain extent he even identi fied with its hero.